2021
DOI: 10.1055/s-0041-1731887
|View full text |Cite
|
Sign up to set email alerts
|

Does Growth Stunting Correlate with Oral Health in Children?: A Systematic Review

Abstract: Growth stunting is when children tend to be shorter than their peers through the World Health Organization child growth standard measurement. The condition may affect the development of the brain and other parts of the body, including the oral cavity, which manifests in oral hygiene and overall oral health. This systematic approach literature study aimed to evaluate the correlation between growth stunting and oral health in children. This study was conducted by using a literature review method with a systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 24 publications
0
37
0
5
Order By: Relevance
“…1 Growth stunting in toddlers can affect the eruption time of primary teeth and increase the risk of caries. 6 The results of the assessment of the study on the age of appearance of the primary teeth in children with SS showed that the deciduous teeth appeared in children with SS later than in children with NS and much later than in children with TS. These results were obtained from research conducted by Shaweesh and Al-Batayneh in children from 1 to 33 months of age in Jordan who were grouped into three height groups based on the Centers for Disease Control and Prevention (CDC): The United States height-forage growth charts.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…1 Growth stunting in toddlers can affect the eruption time of primary teeth and increase the risk of caries. 6 The results of the assessment of the study on the age of appearance of the primary teeth in children with SS showed that the deciduous teeth appeared in children with SS later than in children with NS and much later than in children with TS. These results were obtained from research conducted by Shaweesh and Al-Batayneh in children from 1 to 33 months of age in Jordan who were grouped into three height groups based on the Centers for Disease Control and Prevention (CDC): The United States height-forage growth charts.…”
Section: Discussionmentioning
confidence: 96%
“…4 During development, malnutrition can affect oral structures. 5,6 Lack of nutrients can cause damage to the enamel which contains higher levels of acidogenic bacteria so that it can facilitate the formation of caries. Nutritional deficiencies can also harm the quantity and quality of saliva, can affect the process of tooth eruption and tooth loss, and can affect the integrity of the soft tissues in the oral cavity.…”
Section: Introductionmentioning
confidence: 99%
“…However, malnutrition that involves a lack of protein-energy also increases the risk of salivary gland dysfunction and enamel hypoplasia, which eventually causes caries in the primary teeth of children ( 65 ). The nutritional status of children in the first thousand days of life is related to dental and oral health ( 66 , 67 ).…”
Section: Linking Fetal Undernutrition That Yields To Neonatal Stuntin...mentioning
confidence: 99%
“…Wasting and stunting are associated with the risk of developing enamel defects and increased plaque accumulation. [6,7] Another study shows that caries causing pain and resulting with tooth loss can affect a child's ability to eat, can disrupt his/her sleep time, and can cause discomfort. So, nutritional status and ECC may have a two-way correlation.…”
Section: Introductionmentioning
confidence: 99%